1985
DOI: 10.1095/biolreprod33.3.729
|View full text |Cite
|
Sign up to set email alerts
|

An Autoradiographic Study of Rabbit Ovarian Surface Epithelium Before and After Ovulation1

Abstract: Morphologic studies suggest that the proliferative activity of the ovarian surface epithelium (OSE) may vary during the reproductive life cycle. To further investigate this phenomenon, rabbit ovaries obtained before and after induction of ovulation with human chorionic gonadotropin (hCG) were incubated in medium containing 3H-methylthymidine and processed for autoradiography. Before ovulation, the labeling index (LI) of OSE cells varied from 0.04% to 0.22%. Twelve hours after hCG, the maximal LI (9.02 +/- 0.38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 0 publications
1
30
0
1
Order By: Relevance
“…In addition, both FSH and hCGlike hormones increase KL mRNA expression in granulosa cells of mice (Motro and Bernstein, 1993) and rats (Ismail et al, 1996). Although there is evidence that OSE cells express receptors for both LH (Osterholzer et al, 1985) and FSH (Zheng et al, 1996), the immortalized OSE cell line used in this study does not express these receptors (manuscript in preparation). However, cAMP serves as the second messenger following receptor activation by both gonadotropins, and activation of this signalling pathway can be mimicked by dbcAMP.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, both FSH and hCGlike hormones increase KL mRNA expression in granulosa cells of mice (Motro and Bernstein, 1993) and rats (Ismail et al, 1996). Although there is evidence that OSE cells express receptors for both LH (Osterholzer et al, 1985) and FSH (Zheng et al, 1996), the immortalized OSE cell line used in this study does not express these receptors (manuscript in preparation). However, cAMP serves as the second messenger following receptor activation by both gonadotropins, and activation of this signalling pathway can be mimicked by dbcAMP.…”
Section: Discussionmentioning
confidence: 84%
“…Normal human OSE express specific receptors for FSH and LH/hCG both in vivo and in vitro (42)(43)(44). However, the findings regarding the effect of FSH and LH/hCG on OSE are inconsistent; treatment with gonadotropins stimulated OSE proliferation in some studies (43,(45)(46)(47) but was either noneffective (16) or inhibitory for other cases (48). In this study, we observed changes in N-cadherin levels at concentrations of FSH that correlate with the profile of serum concentration of FSH and LH/hCG in the normal reproductive cycle.…”
Section: Inhibitor Of Matrix Metalloproteinase Inhibits the Camp-medimentioning
confidence: 99%
“…Prior to ovulation, OSE proliferation increases at sites adjacent to follicular development (Bjersing & Cajander 1974, Burdette et al 2006) and ovulationrelated desquamation of the surface epithelial cells involves programmed cell death or apoptosis (Bjersing & Cajander 1975, Ackerman & Murdoch 1993, Murdoch 1994, 1995. Following ovulation, the wound at the ovarian surface is rapidly repaired by proliferation of the OSE from the perimeter of the ruptured follicle, and ovarian epithelial cells have also been postulated to be involved in the deposition and restructuring of the extracellular matrix of the tunica albuginea (Motta 1980, Osterholzer et al 1985, Kruk & Auersperg 1992, Gaytan et al 2005, Burdette et al 2006. The constant rounds of proliferation and repair following ovulation provide the opportunity for replication errors and dysregulation of the genes involved in the normal processes of proliferation, apoptosis, and DNA repair, and thus may contribute to neoplastic progression in the OSE (Fathalla 1971).…”
Section: Introductionmentioning
confidence: 99%